No Magic Bullets: Insights on Drivers of Stunting Decline from an Analysis of Subnational Success Cases in India - Avula, Rasmi; Nguyen, Phuong H.; Menon, Purnima (2021)
Rasmi Avula, Phuong Nguyen, Purnima Menon POLICY SEMINAR Tackling child undernutrition at scale: Insights from national and subnational success cases Co-Organized by IFPRI and Exemplars in Global Health APR 1, 2021 - 09:30 AM TO 11:00 AM EDT